Selective Predation of a Stalking Predator on Ungulate Prey - Heurich, Marco; Zeis, Klara; Küchenhoff, Helmut; Müller, Jörg; Belotti, Elisa; Bufka, Luděk; Woelfing, Benno (PLoS One, 2016)
Prey selection is a key factor shaping animal populations and evolutionary dynamics. An optimal forager should target prey that offers the highest benefits in terms of energy content at the lowest costs. Predators are therefore expected to select for prey of optimal size. Stalking predators do not pursue their prey long, which may lead to a more random choice of prey individuals. Due to difficulties in assessing the composition of available prey populations, data on prey selection of stalking carnivores are still scarce. We show how the stalking predator Eurasian lynx (Lynx lynx) selects prey individuals based on species identity, age, sex and individual behaviour. To address the difficulties in assessing prey population structure, we confirm inferred selection patterns by using two independent data sets: (1) data of 387 documented kills of radio-collared lynx were compared to the prey population structure retrieved from systematic camera trapping using Manly's standardized selection ratio alpha and (2) data on 120 radio-collared roe deer were analysed using a Cox proportional hazards model. Among the larger red deer prey, lynx selected against adult males-the largest and potentially most dangerous prey individuals. In roe deer lynx preyed selectively on males and did not select for a specific age class. Activity during high risk periods reduced the risk of falling victim to a lynx attack. Our results suggest that the stalking predator lynx actively selects for size, while prey behaviour induces selection by encounter and stalking success rates.
Keywords: Sex Factors; Deer; Predatory Behavior; vysoká zvěř; proporcionální rizikové modely; Population Dynamics; Proportional Hazards Models; Food Chain; Ecosystem; predátorské chování; výběrové chování; Female; věkové faktory; Lynx; stalking; velikost těla; zvířata; Stalking; sexuální faktory; populační dynamika; Choice Behavior; roční období; ženské pohlaví; Male; Seasons; Body Size; Age Factors; Animals; mužské pohlaví; potravní řetězec; ekosystém